2020
DOI: 10.1177/1759091420938175
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Susceptibility to Chemoconvulsant-Induced Seizures in Ganglioside GM3 Synthase Knockout Mice

Abstract: Ganglioside GM3 synthase (α-2,3-sialyltransferase, ST3GAL5, GM3S) is a key enzyme involved in the biosynthesis of gangliosides. ST3GAL5 deficiency causes an absence of GM3 and all downstream biosynthetic derivatives. The affected individuals manifest deafness, severe irritability, intractable seizures, and profound intellectual disability. To investigate whether deficiency of GM3 is involved in seizure susceptibility, we induced seizures with different chemoconvulsants in ST3GAL5 knockout mice. We report here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The changes reported here are in keeping with the demonstration of hyperactivity in juvenile male St3gal5 −/− mice bred on C57BL/6-129/sv [ 3 , 14 ] and C57BL/6 [ 15 ] backgrounds. The open-field hyperlocomotion of the St3gal5 −/− mutants was also previously reported in juvenile mice of both sexes [ 21 ], which is consistent with our observations here. Niimi et al [ 14 ] found no effect of the administration of psychostimulant methylphenidate on the hyperactivity of juvenile St3gal5 −/− mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The changes reported here are in keeping with the demonstration of hyperactivity in juvenile male St3gal5 −/− mice bred on C57BL/6-129/sv [ 3 , 14 ] and C57BL/6 [ 15 ] backgrounds. The open-field hyperlocomotion of the St3gal5 −/− mutants was also previously reported in juvenile mice of both sexes [ 21 ], which is consistent with our observations here. Niimi et al [ 14 ] found no effect of the administration of psychostimulant methylphenidate on the hyperactivity of juvenile St3gal5 −/− mice.…”
Section: Discussionsupporting
confidence: 93%
“…Current finding suggests that the changes in the EEG of St3gal5 −/− mutants are similar to those observed in the clinic. As St3gal5 −/− mice showed an increased response to the chemoconvulsants pilocarpine, kainate [ 21 ], and pentylenetetrazole [ 16 ], these changes in EEG may indicate vulnerability for these chemoconvulsant-triggered seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with GM3S mutations have symptomatic epilepsy syndrome with severe neuronal dysfunction (Fragaki et al, 2013; Simpson et al, 2004). To investigate how a deficiency of gangliosides is involved in seizure‐susceptibility, we previously induced seizures with chemoconvulsants (including kainate and pilocarpine) in GM3S‐KO mice (Tang et al, 2020) and found enhanced susceptibility to seizure in GM3S‐KO mice compared to wild‐type mice. In the hippocampal DG, loss of GM3 aggravates seizure‐induced aberrant neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GM3 in turn serves as the precursor for the biosynthesis of numerous other glycolipids, including complex gangliosides that are abundantly found in neuronal tissues. GM3 is enriched in lipid rafts at the plasma membrane and been shown to regulate numerous receptor and integrin‐based signaling pathways 3–8 . Loss of GM3 biosynthesis in GM3SD patients is associated with progressive microcephaly due to impaired neurogenesis, hearing loss, dyskinetic movements, seizures, and variable defects in skin pigmentation 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…GM3 is enriched in lipid rafts at the plasma membrane and been shown to regulate numerous receptor and integrin-based signaling pathways. [3][4][5][6][7][8] Loss of GM3 biosynthesis in GM3SD patients is associated with progressive microcephaly due to impaired neurogenesis, hearing loss, dyskinetic movements, seizures, and variable defects in skin pigmentation. 9,10 The neuronal manifestations of GM3SD reinforce the importance of ganglioside-mediated processes during neurogenesis, and in the maintenance of proper function of neuronal cell types after development.…”
Section: Introductionmentioning
confidence: 99%